Overcoming resistance to immune checkpoint inhibitor in non-small cell lung cancer: the promise of combination therapy - Shi, Xuebing; Deng, Wenxia; Pan, Yunlei; Chen, Yingchun; Wang, Yinke; Wu, Jing (Frontiers in Immunology, 2025)
The clinical application of immune checkpoint inhibitor (ICI) has profoundly reshaped the therapeutic landscape of non-small cell lung cancer (NSCLC), heralding a new era of immunotherapy in oncology. However, despite the durable and remarkable clinical benefits observed in a subset of patients, a considerable proportion exhibit primary or acquired resistance, substantially limiting overall therapeutic efficacy. Immune resistance has emerged as one of the central challenges in ICI-based NSCLC treatment, stemming from an incomplete understanding of ICI mechanisms of action and the highly heterogeneous and dynamically complex nature of the NSCLC tumor microenvironment (TME). This review provides a comprehensive overview of the diverse molecular and cellular mechanisms underlying ICI resistance in NSCLC, highlights recent advances in combination therapeutic strategies aimed at overcoming resistance, and discusses the opportunities and challenges associated with their clinical translation and application.